A Study on the Use of Teaching Media in the Training of Improving Teachersâ Professional Competence - mashoedah, mashoedah (ELINVO, 2015)
The paper discusses a study on the use of teaching media in the teacher trainings, in terms of what media that can be to improve teachersâ professional competence.Â  Â The methods used were a literature review and online survey conducted among teachers in the teacher group in the social media network. The use online research was expected to be able to explore the teachersâ responses to the use of appropriate teaching media and other problems related to the improvement of their professional competence.Â The results showed that the problem mostly faced by teachers are the improvement of the teacherâs competence of expertise (42%), the minimum availability of teaching media at school (24%), curriculum (15%) and other problems (19%). The teachers expected that the teaching media used in the teacher trainings areÂ  in the forms of Â a combination of media (49%) , videosÂ  (29%), e-learningÂ  (15%), and Â trainer kit (6%). The expected model of media used in the teacher trainings to improve the professional competence is the integration of various teaching media.Â Â